Wasser - Hoenecke, Christian; Scholz, Gerold 1944- (Cornelsen Verlag, 1990)
Student book about water: how it flows, surface tension, frozen water and water vapor, sounds made by water, clouds, water cycle, water purification and conservation. Includes activities, reading exercises, a song, and a game.
Keywords: German language materials; Hydrology; Water; Water supply